Pragmatic Sentiments and Coping Strategies of Out-Of-Field English Teachers in Public Senior High Schools - Glady Cidro Lagria (CV. Literasi Indonesia, 2021)
A phenomenological study was conducted to examine the challenges of out-of-field teachers in English, including their coping mechanisms and their suggested solutions to manage their sentiments in public senior high schools during the school year 2019-2020. The researcher used a one-on-one interview guide in collecting data, which were analyzed using the Ajjawi and Higgs framework of data analysis. The lack of content mastery that results in poor students’ performance is the top sentiment for out-of-field teachers, and it was hard for them to teach English as it is out of their specialization. It was found out that the out-of-field teachers employed several coping strategies and suggested solutions to DepEd to manage their sentiments, such as; acquiring competence through training, self-learning and motivating, asking for assistance from co-teachers, and to improve schools’ manpower. Hence, the researcher recommends the conduct of a comparative study on the performance of students and teachers, and regular mentoring of school heads and master teachers to aid out-of-field teachers. This calls for program mechanics that deal with alleviating the challenges that novice out-of-field teachers experience through program reforms, training and skills enhancement, professional development, and peer mentoring programs.